2022
DOI: 10.3390/antiox11101927
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Immune Stimulating Effects of Allium hookeri Extracts in the RAW 264.7 Cells and Immune-Depressed C57BL/6 Mice

Abstract: We investigated the antioxidant and immune-enhancing effects of the extracts from Allium hookeri leaves and roots (AHL and AHR) in in vitro and in vivo models. Their antioxidant effects were determined by total phenolic content (TPC), DPPH and ABTS radical scavenging activities, and superoxide dismutase and catalase activities. The immunomodulatory effects were evaluated by nitric oxide (NO) production and cytokine concentrations produced from RAW 264.7, and by serum IgA and IgG levels, cytokine levels, and NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The final body weights of mice treated with A. hookeri leaf extracts increased and were comparable to those of the NOR group, which was not immunosuppressed with CPA. In a previous study, the administration of A. hookeri leaf and root extracts improved the final body weights of immunosuppressed mice [ 35 ]. A. hookeri leaf groups showed higher spleen and thymus weights than those of the NC group among all immunosuppressed mice and reached those of the NOR group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final body weights of mice treated with A. hookeri leaf extracts increased and were comparable to those of the NOR group, which was not immunosuppressed with CPA. In a previous study, the administration of A. hookeri leaf and root extracts improved the final body weights of immunosuppressed mice [ 35 ]. A. hookeri leaf groups showed higher spleen and thymus weights than those of the NC group among all immunosuppressed mice and reached those of the NOR group.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigated that A. cepa skin and P. basummii improved NK cell activity in the blood, spleen, and peritoneal cells of immunosuppressed mice [ 42 , 44 ]. A. hookeri leaves and roots stimulated NK cell activity against Yac-1 in splenocytes of immunosuppressed mice [ 35 ]. The mild NK cell activities in the A. hookeri leaf groups may be explained with the relatively lower CPA treatment at 100 mg/kg BW by 2 times on −3 and −1 day before the experiment, which were treated at 150 and 100 mg/kg BW in previous trials for the immunosuppressed model.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study reported that the NO production of onion and methanol extract from onion was 1.09 μM and 1.41 μM at 1000 μg/mL, respectively [ 46 ]. A. hookeri stimulated the production of NO in RAW 264.7 cells [ 18 , 47 ]. NO regulates the adaptive immune response and depresses or stimulates the pro-inflammatory cytokine expression [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The spleen, a lymphoid organ, constitutes the main filter of the body of blood-borne antigens, and the site of differentiation and homing of inflammatory macrophages, granulocytes, and NK cells [ 64 ]. In the previous study, the extract of A. hookeri leaves and roots improved the proliferation of splenocytes [ 18 ]. The polysaccharide of Cyclocarya paliurus recovered the proliferation of splenocytes in CPA-induced immunosuppression mice model in the presence of Con A and LPS [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation